2014
DOI: 10.1127/0003-5548/2014/0366
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the enamel hypoplasia using micro-CT scanner versus classical method

Abstract: This article demonstrates the use of micro-CT scanning of the teeth surface for recognizing and evaluating severity of the enamel hypoplasia. To test capabilities of the microtomography versus classical method of evaluation hypoplastic defects of the enamel we selected two human teeth (C, M(2)) showing different types of enamel hypoplasia: linear, pits, and groove. Examined samples derive from archeological material dated on XVII-XVIII AD and excavated in Poland. In the current study we proved that micro-CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…However, all qualitatively identified LEH defect depths fall completely outside the distribution of perikymata depths (Figure ). New research addresses the problem of defining normal vs. abnormal surface morphology on the basis of perikymata spacing via measuring microscope, SEM, and focus variation microscopy (Bocaege & Hillson, ; Bocaege et al ; King et al, ; Temple et al, 2013), and on the basis of depth using microCT scans (Marchewka et al, ), digital microscopy (Skinner & Pruetz, 2012), ) or a measuring microscope (Henriquez & Oxenham, ). A challenge with identifying wider‐than‐average perikymata is that even slight deviations from “normal” spacing are flagged as potential LEH defects (Bocaege & Hillson, ; Hassett ; Hillson, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all qualitatively identified LEH defect depths fall completely outside the distribution of perikymata depths (Figure ). New research addresses the problem of defining normal vs. abnormal surface morphology on the basis of perikymata spacing via measuring microscope, SEM, and focus variation microscopy (Bocaege & Hillson, ; Bocaege et al ; King et al, ; Temple et al, 2013), and on the basis of depth using microCT scans (Marchewka et al, ), digital microscopy (Skinner & Pruetz, 2012), ) or a measuring microscope (Henriquez & Oxenham, ). A challenge with identifying wider‐than‐average perikymata is that even slight deviations from “normal” spacing are flagged as potential LEH defects (Bocaege & Hillson, ; Hassett ; Hillson, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, variation in the internal geometry of underlying enamel growth increments may also influence defect depth (Guatelli‐Steinberg et al, ). While histological analysis is the only way to obtain a complete understanding of how individual defects formed (Witzel, Kierdorf, Schultz, & Kierdorf, ), nondestructive imaging‐based methods have been developed to quantitatively characterize defect morphology from the outer enamel surface (Bocaege & Hillson, ; Bocaege, Humphrey, & Hillson, ; Guatelli‐Steinberg, Larsen, & Hutchinson, ; Hassett, ; Henriquez & Oxenham, ; Hillson, ; Hillson & Jones, ; King, Hillson, & Humphrey, , Le Cabec, Tang, & Tafforeau, ; Marchewka, Skrzat, & Wróbel, ; Skinner & Pruetz, ; Skinner & Skinner, ; Temple, McGroarty, Guatelli‐Steinberg, Nakatsukasa, & Matsumura, ). These methods have the potential to reduce interobserver error in the identification and characterization of defects, but fundamental questions remain about the extent of inter‐ and intraspecific variation in defect morphology in primates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For LEHs, initial observations were performed using the binocular microscope and SEM. Then, on each micro‐CT‐reconstructed tooth, LEH defects were identified as bands on the full 3D reconstruction that could be matched to depressions on sagittal cross‐sections of the enamel surface (Marchewka et al, ) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The first is to systematically document and describe enamel defects in the Xujiayao juvenile as identified using binocular, scanning electron microscopy (SEM) and micro‐computed tomography (micro‐CT) imaging techniques. Recently, Marchewka et al () demonstrated that enamel defects that were not visible using SEM or light microscopy could be clearly identified using micro‐CT. Here, we evaluate differences among the three methods used to identify enamel defects.…”
Section: Introductionmentioning
confidence: 99%